Identifikasi Risiko Usahatani Cabai Merah di Kabupaten Aceh Besar - Hamzah Al Pansuri; Rahmaddiansyah Rahmaddiansyah; Sofyan Sofyan (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Red chili farming is an activity that is mostly carried out by rural communities in Aceh Province. Aceh Besar Regency is one of the regencies in Aceh Province and is the central producer of red chili in Aceh Province but cannot be separated from the various risks that threaten it. There are several risks faced by farmers originating from several risk factors that result in a decrease in production and productivity of large chilies as well as price conditions that can also affect farmers' income. These risk factors include production, price and marketing risk factors, finance, constitution and human Resources. However, not all risks should be prioritized for risk management considering the many risks that will be faced and the limited resources and time of farmers in preparing risk management. The purpose of this study is to find out what risks are faced by farmers and determine the most priority risks for risk management for red chili farming in Aceh Besar District, which is represented by 2 sub-districts, namely Kuta Cot Glie and Seulimeum Districts. From these two sub-districts, three villages will be selected to represent each of these sub-districts, namely the villages of Lamtui, Banda Safa and Ie Alang Dayah representing the Kuta Cot Glie sub-district, then the villages of Bayu, Ayon and Alu Rindang representing the Seulimeum sub-district. The choice of the location of this research was done intentionally (purposive), with a sample of 60 farmers. The data used are primary data and secondary data. The analysis method uses descriptive methods and FMEA (Failure Mode and Effect Analysis) methods.The results showed that there were 21 risks faced by farmers and based on the calculation of the RPN value (Risk Priority Number) then there are 3 risks that must be prioritized. The risk that must be prioritized first is the attack of fruit rot with an RPN value of 57.08, the second is the high rainfall caused by the rainy season with a RPN value of 32.63, the third is the decline in prices due to the harvest with an RPN value of 31.05.